Energy-saving and environment-friendly furnace top nano heat-preservation castable
By using modified fibers in the furnace top castable material combined with nano-insulating materials, the problems of high energy consumption and low environmental protection during the preparation of lightweight thermal insulation bricks are solved, and the goals of improving efficient insulation performance and energy conservation and environmental protection are achieved.
Patent Information
- Application Number
- CN202411852407.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lightweight thermal insulation bricks consume high energy and are environmentally friendly during the preparation process, and lack compressive strength and flame retardancy in high temperature environments, making it difficult to meet the needs of energy-saving, environmentally friendly and efficient insulation.
Combining modified fibers with nano-insulating materials is used to prepare energy-saving and environmentally friendly furnace top nano-insulating castables. The modified fibers improve the flame retardancy and high temperature resistance of the fibers through grafting reactions, and combine them with nano-insulating materials to improve the overall performance of the castable.
It realizes the efficient insulation performance of the castable material, improves its compressive strength, high temperature resistance and flame retardancy, reduces energy consumption during sintering, and meets the requirements of energy conservation and environmental protection.
Smart Images

Figure BDA0005190924750000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of castables, and in particular to energy-saving and environment-friendly furnace top nano thermal insulation castables. Background Art
[0002] In the prior art, lightweight thermal insulation bricks are widely used as thermal insulation filling materials between refractory bricks and ketone bodies in various industrial furnaces due to their high porosity, low bulk density and good thermal insulation performance, so as to reduce heat loss in the furnace and obtain high energy utilization efficiency. However, the preparation process of lightweight thermal insulation bricks involves a high-temperature sintering process, which has the disadvantages of high energy consumption and low environmental protection, and does not meet the current requirements of energy conservation and environmental protection.
[0003] Castables play an indispensable role in the construction and maintenance of industrial furnaces. Due to their high fluidity, good fire resistance, thermal shock resistance and compressive strength, castables are widely used in the construction of furnace walls, furnace roofs and furnace bottoms. Furnace roof castables belong to building refractory materials. They are granular and powdery materials made of refractory materials with a certain amount of adhesives and additives. They can not only withstand thermal stress in high temperature environments, but also effectively reduce heat loss and improve the thermal efficiency of the furnace.
[0004] Nano thermal insulation material is a new type of thermal insulation material, which is usually prepared from a variety of nano-silicon and micron-level siliceous raw materials. It has a multi-level pore structure, high specific surface area, excellent thermal conductivity and good thermal insulation performance, and can achieve efficient thermal insulation and heat insulation effects. Nanoporous thermal insulation material is a new type of thermal insulation material obtained by a series of physical and chemical reactions of fumed silica, infrared sunscreen, fiber, etc. It has excellent thermal insulation and heat preservation effects due to a large number of nano-level micropores inside. In the prior art, organic reinforcing fibers such as polyethylene and polypropylene are often used to improve the compressive strength of nanoporous thermal insulation materials. The molecular chains of organic reinforcing fibers such as polyethylene and polypropylene do not have polar groups, and their compatibility with other components such as fumed silica is poor. In addition, organic reinforcing fibers such as polyethylene and polypropylene have poor high temperature resistance and flame retardancy, which is not conducive to their use in nano thermal insulation materials and furnace top castables.
[0005] Therefore, it is of practical significance to apply organic reinforcing fibers with improved flame retardancy, high temperature resistance and dispersibility to nano thermal insulation materials, and then add the nano thermal insulation materials to furnace roof castables to prepare furnace roof castables with thermal insulation effects and excellent comprehensive performance. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an energy-saving and environment-friendly furnace top nano thermal insulation castable.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] Energy-saving and environment-friendly furnace top nano thermal insulation castable, comprising the following raw materials in parts by weight: 13-15 parts of hollow microspheres, 2-4 parts of nano thermal insulation materials, 20-25 parts of perlite, 32-35 parts of coke gemstones, 5-7 parts of activated alumina micropowder, 5-7 parts of soft clay, 20-22 parts of high-temperature cement, 3-5 parts of expansion agent, and 0.3-0.4 parts of water reducing agent;
[0009] The soft clay is soft kaolin, the expansion agent is selected from one of kyanite and quartz, and the water reducing agent is selected from one of sodium tripolyphosphate and sodium hexametaphosphate;
[0010] The nano thermal insulation material comprises the following raw materials in parts by weight: 60-80 parts of fumed silica, 20-30 parts of titanium dioxide, 5-7 parts of glass fiber, and 3-5 parts of modified fiber;
[0011] The energy-saving and environment-friendly furnace top nano thermal insulation castable is prepared by the following steps:
[0012] Step S1: stirring fumed silica, titanium dioxide, glass fiber and modified fiber for 20-30 minutes to obtain a mixture, then putting the mixture into a grinder and grinding it for 1-1.5 hours, then transferring it to a mixer and mixing it at 150-170° C. for 40-50 minutes, and drying it to obtain a nano thermal insulation material;
[0013] Step S2: the hollow microspheres, nano thermal insulation material, perlite, coke gemstone, activated alumina powder, soft clay, high temperature cement, expansion agent and water reducing agent are stirred and mixed for 1-1.5 hours, vibrated and molded, cured at room temperature for 24-26 hours, and then kept warm at 100-120° C. for 24-26 hours to obtain energy-saving and environmentally friendly furnace top nano thermal insulation castable.
[0014] The modified fiber is prepared by the following steps:
[0015] Step A1: In a protective gas atmosphere, add a triazine-containing carboxylic acid to ethyl acetate, heat to 50-60°C, add pyridine, start stirring, then add epoxy POSS, stir to react for 10-12h, then heat to 110-120°C, stir for 1-2h to obtain a hydroxyl product;
[0016] Further, the amount ratio of the triazine-containing carboxylic acid, ethyl acetate, pyridine, and epoxy POSS is 0.1-0.15 mol: 130-140 mL: 2-4 g: 49-51 g, the triazine-containing carboxylic acid is selected from one of 1,3,5-triazine-2-carboxylic acid, 1,2,3-triazine-5-carboxylic acid, and 1,2,4-triazine-3-carboxylic acid, and the epoxy POSS is Γ-glycidyl ether oxygen silyl propyl sesquioxane;
[0017] During the reaction of step A1, the carboxyl group of the triazine-containing carboxylic acid reacts with the epoxy group of the epoxy POSS to obtain a hydroxyl product containing triazine and POSS;
[0018] Step A2: Add a carboxylic acid containing a terminal double bond to DMF, add dichlorothionyl under stirring, reflux and stir at 45-50° C. for 4-5 hours to obtain an acyl chloride product; add a hydroxyl product, pyridine and triethylamine to dimethyl sulfoxide, stir and mix to obtain a mixed solution 1; add the acyl chloride product to dimethyl sulfoxide and stir and mix to obtain a mixed solution 2; in a 0° C. ice water bath, dropwise add the mixed solution 2 to the mixed solution 1; after the dropwise addition is completed, heat to 40-45° C., stir and react at a constant temperature for 8-10 hours, then heat to 100-110° C., continue stirring for 1-1.5 hours, and distill under reduced pressure to obtain a functional monomer;
[0019] Further, the amount ratio of the carboxylic acid containing a terminal double bond, DMF, and dichlorothionyl is 0.1-0.12 mol: 60-70 mL: 0.13-0.15 mol, and the carboxylic acid containing a terminal double bond is selected from 7-octenoic acid, 9-decenoic acid, and undecenoic acid; the amount ratio of the hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in the mixed solution 1 is 17-20 g: 0.01-0.015 mol: 0.05-0.07 mol: 80-90 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution 2 is 15-19 g: 30-40 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 85-95 mL: 35-45 mL;
[0020] During the reaction of step A2, the carboxylic acid containing a terminal double bond reacts with thionyl chloride to generate an acyl chloride product; the acyl chloride product then reacts with a hydroxyl product to obtain a functional monomer containing a terminal carbon-carbon double bond;
[0021] Step A3: In a protective gas atmosphere, add the functional monomer and cross-linking agent to toluene, stir for 10-15 minutes, add the organic fiber and continue stirring for 10-15 minutes, seal and 60 After irradiation with Coγ-rays for 8-10 hours, the organic fibers are taken out, washed with anhydrous ethanol, extracted with acetone, and dried to obtain modified fibers;
[0022] Furthermore, the usage ratio of toluene, functional monomer, crosslinking agent and organic fiber is 400-450mL: 35-40g: 10-12g: 100-110g, the organic fiber is selected from one of polyethylene fiber and polypropylene fiber, and the crosslinking agent is divinylbenzene;
[0023] During the reaction of step A3, 60 Under the irradiation of Coγ-rays and the assistance of crosslinking agent, the functional monomers are grafted onto the organic fibers to obtain modified fibers.
[0024] Beneficial effects of the invention: The invention discloses an energy-saving and environment-friendly furnace top nano thermal insulation castable, which is prepared from hollow microspheres, nano thermal insulation materials, perlite, coke gemstones, activated alumina micropowder, soft clay, high-temperature cement, expansion agent, water reducing agent, etc. The nano thermal insulation material includes raw materials such as fumed silica, titanium dioxide, glass fiber and modified fiber.
[0025] The synthesized modified fiber is obtained by grafting functional monomers containing terminal carbon-carbon double bonds, triazine and POSS onto organic fibers. When triazine flame retardants containing triazine rings burn, they can not only release non-combustible gases such as nitrogen and carbon dioxide, which can dilute combustible gases and reduce the combustion rate, but also form a carbon layer that isolates oxygen and heat, preventing the fire source from contacting the castable, thereby preventing combustion; POSS can form a ceramic layer with heat insulation and oxygen isolation during the combustion process to prevent further combustion. POSS and triazine rings produce intramolecular synergy, synergistic flame retardancy in the gas phase and condensed phase, giving organic fibers excellent flame retardancy; the POSS structure has excellent structural stability and thermal stability. After the organic fiber is grafted with POSS, the high temperature resistance of the organic fiber is significantly improved, making the modified fiber more suitable for use in nano thermal insulation materials. Compared with organic fibers, the compatibility of the modified fiber with components such as fumed silica and titanium dioxide is enhanced, which is more conducive to the improvement of the strength of the nano thermal insulation material by the organic fiber, thereby maintaining the good thermal insulation performance of the nano thermal insulation material. The nano thermal insulation material prepared using the modified fiber is applied to the energy-saving and environment-friendly furnace top nano thermal insulation castable of the present invention, which is helpful to improve the compressive strength, high temperature resistance and flame retardancy of the castable.
[0026] Compared with the traditional use of lightweight thermal insulation bricks for furnace roof insulation, the thermal insulation castable of the present invention reduces energy-intensive processes such as sintering, meets the requirements of energy conservation and environmental protection, and adds nano-insulation materials with thermal insulation properties to the castable to give the castable excellent thermal insulation properties. The resulting energy-saving and environmentally friendly furnace roof nano-insulation castable has good integrity and is more convenient to construct, and is worthy of promotion and use in the field of furnace roof insulation castables. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A modified fiber, the preparation of which comprises the following steps:
[0030] Step A1: In a nitrogen atmosphere, add 1,3,5-triazine-2-carboxylic acid to ethyl acetate, heat to 50°C, add pyridine, start stirring, then add γ-glycidyloxysilylpropylsesquioxane, stir and react for 10 hours, then heat to 110°C, stir for 1 hour to obtain a hydroxyl product; the amount ratio of 1,3,5-triazine-2-carboxylic acid, ethyl acetate, pyridine, and epoxy POSS is 0.1 mol: 130 mL: 2 g: 49 g;
[0031] Step A2: 7-octenoic acid was added to DMF, and dichlorothionyl was added under stirring, and the mixture was refluxed and stirred at 45°C for 4 hours to obtain an acyl chloride product; the hydroxyl product, pyridine and triethylamine were added to dimethyl sulfoxide, and the mixture was stirred to obtain a mixed solution 1; the acyl chloride product was added to dimethyl sulfoxide and stirred to obtain a mixed solution 2, and the mixed solution 2 was added dropwise to the mixed solution 1 in a 0°C ice-water bath. After the addition was completed, the mixture was heated to 40°C, stirred at a constant temperature for 8 hours, and then heated to 100°C and stirred continuously. Stir for 1h, and distill under reduced pressure to obtain the functional monomer; the dosage ratio of 7-octenoic acid, DMF, and dichlorothionyl is 0.1mol:60mL:0.13mol; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution 1 is 17g:0.01mol:0.05mol:80mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 15g:30mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 85mL:35mL;
[0032] Step A3: In a nitrogen atmosphere, add the functional monomer and divinylbenzene to toluene, stir for 10 min, add polyethylene fiber and continue stirring for 10 min, seal and 60 After 8 hours of Coγ-ray irradiation, the fiber was taken out and rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified fiber; the dosage ratio of toluene, functional monomer, divinylbenzene and polyethylene fiber was 400mL:35g:10g:100g.
[0033] Example 2
[0034] A modified fiber, the preparation of which comprises the following steps:
[0035] Step A1: In a nitrogen atmosphere, add 1,2,3-triazine-5-carboxylic acid to ethyl acetate, heat to 55°C, add pyridine, start stirring, then add γ-glycidyloxysilylpropylsesquioxane, stir to react for 11 hours, then heat to 115°C, stir for 1.5 hours to obtain a hydroxyl product; the amount ratio of 1,2,3-triazine-5-carboxylic acid, ethyl acetate, pyridine, and γ-glycidyloxysilylpropylsesquioxane is 0.13 mol: 135 mL: 3 g: 50 g;
[0036] Step A2: 9-decenoic acid was added to DMF, and dichlorothionyl was added under stirring, and the mixture was refluxed and stirred at 47°C for 4.5 hours to obtain an acyl chloride product; the hydroxyl product, pyridine and triethylamine were added to dimethyl sulfoxide, and the mixture was stirred to obtain a mixed solution 1; the acyl chloride product was added to dimethyl sulfoxide and stirred to obtain a mixed solution 2, and the mixed solution 2 was added dropwise to the mixed solution 1 in a 0°C ice water bath. After the addition was completed, the mixture was heated to 43°C, stirred at a constant temperature for 9 hours, and then heated to 105°C and stirred for 1 hour. .3h, and distill under reduced pressure to obtain the functional monomer; the dosage ratio of 9-decenoic acid, DMF, and dichlorothionyl is 0.11mol:65mL:0.14mol; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution 1 is 18.5g:0.013mol:0.06mol:85mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 17g:35mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 90mL:40mL;
[0037] Step A3: In a nitrogen atmosphere, add the functional monomer and divinylbenzene to toluene, stir for 13 minutes, add polypropylene fiber and continue stirring for 13 minutes, seal and 60 After irradiation with Coγ rays for 9 hours, the fiber was taken out and the modified fiber was obtained by washing with anhydrous ethanol, extracting with acetone and drying. The usage ratio of toluene, functional monomer, divinylbenzene and polypropylene fiber was 430mL:37g:11g:105g.
[0038] Example 3
[0039] A modified fiber, the preparation of which comprises the following steps:
[0040] Step A1: In a nitrogen atmosphere, add 1,2,4-triazine-3-carboxylic acid to ethyl acetate, heat to 60°C, add pyridine, start stirring, then add γ-glycidyloxysilylpropylsesquioxane, stir to react for 12h, then heat to 120°C, stir for 2h to obtain a hydroxyl product; the amount ratio of 1,2,4-triazine-3-carboxylic acid, ethyl acetate, pyridine, and γ-glycidyloxysilylpropylsesquioxane is 0.15mol:140mL:4g:51g;
[0041] Step A2: undecylenic acid is added to DMF, and dichlorothionyl is added under stirring, and the mixture is refluxed and stirred at 50°C for 5 hours to obtain an acyl chloride product; the hydroxyl product, pyridine and triethylamine are added to dimethyl sulfoxide, and the mixture is stirred to obtain a mixed solution 1; the acyl chloride product is added to dimethyl sulfoxide and stirred to obtain a mixed solution 2, and the mixed solution 2 is added dropwise to the mixed solution 1 in a 0°C ice water bath. After the addition is completed, the mixture is heated to 45°C, stirred at a constant temperature for 10 hours, and then heated to 110°C and stirred continuously. 1.5h, vacuum distillation, that is, functional monomers are obtained; the dosage ratio of undecylenic acid, DMF, and dichlorothionyl is 0.12mol:70mL:0.15mol; the dosage ratio of hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide in mixed solution 1 is 20g:0.015mol:0.07mol:90mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 19g:40mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 95mL:45mL;
[0042] Step A3: In a nitrogen atmosphere, add the functional monomer and divinylbenzene to toluene, stir for 15 minutes, add polypropylene fiber and continue stirring for 15 minutes, seal and 60 After 10 hours of Coγ-ray irradiation, the fiber was taken out and rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified fiber; the dosage ratio of toluene, functional monomer, divinylbenzene and polypropylene fiber was 450mL:40g:12g:110g.
[0043] Example 4
[0044] Energy-saving and environment-friendly furnace top nano thermal insulation castable, including the following raw materials by weight: 13 parts of hollow microspheres, 2 parts of nano thermal insulation materials, 20 parts of perlite, 32 parts of coke gemstones, 5 parts of activated alumina micropowder, 5 parts of soft clay, 20 parts of high-temperature cement, 3 parts of expansion agent, and 0.3 parts of water reducing agent;
[0045] The nano thermal insulation material comprises the following raw materials in parts by weight: 60 parts of fumed silica, 20 parts of titanium dioxide, 5 parts of glass fiber, and 3 parts of modified fiber;
[0046] The energy-saving and environment-friendly furnace top nano thermal insulation castable is prepared by the following steps:
[0047] Step S1: stirring fumed silica, titanium dioxide, glass fiber and the modified fiber obtained in Example 1 for 20 minutes to obtain a mixed material, then putting the mixed material into a grinder and grinding it for 1 hour, then transferring it to a mixer and mixing it at 150° C. for 40 minutes, and drying it to obtain a nano thermal insulation material; the fumed silica (supplier: Shandong Wanhua Tianhe New Materials Co., Ltd.) and the glass fiber (supplier: Changzhou Bochao Engineering Materials Co., Ltd.);
[0048] Step S2: Stir and mix the hollow microspheres, nano thermal insulation material, perlite, coke gemstones, activated alumina powder, soft clay, high temperature cement, expansion agent and water reducer for 1 hour, vibrate to form, cure at room temperature for 24 hours, and then keep warm at 100°C for 24 hours to obtain an energy-saving and environmentally friendly furnace top nano thermal insulation castable; the hollow microspheres (supplier: Shijiazhuang Mayue Building Materials Co., Ltd., 30 mesh), perlite (supplier: Lingshou County Baisheng Mineral Products Co., Ltd., item number 0351), coke gemstones (supplier: Zibo Ouyihui Refractory Materials Co., Ltd.), activated alumina powder (supplier: Shanghai Yuanjiang Chemical Co., Ltd.), soft clay is soft kaolin (supplier: Shijiazhuang Huijin Mineral Products Co., Ltd.), high temperature cement (supplier: Changzhou Painuomen Thermal Conductive Materials Co., Ltd.), the expansion agent is kyanite (supplier: Henan Jingchuan Kyanite Mining Co., Ltd.), and the water reducer is sodium tripolyphosphate.
[0049] Example 5
[0050] Energy-saving and environment-friendly furnace top nano thermal insulation castable, including the following raw materials by weight: 14 parts of hollow microspheres, 3 parts of nano thermal insulation materials, 23 parts of perlite, 33 parts of coke gemstones, 6 parts of activated alumina micropowder, 6 parts of soft clay, 21 parts of high-temperature cement, 4 parts of expansion agent, and 0.4 parts of water reducing agent;
[0051] The nano thermal insulation material comprises the following raw materials in parts by weight: 70 parts of fumed silica, 25 parts of titanium dioxide, 6 parts of glass fiber, and 4 parts of modified fiber;
[0052] The energy-saving and environment-friendly furnace top nano thermal insulation castable is prepared by the following steps:
[0053] Step S1: stirring fumed silica, titanium dioxide, glass fiber and the modified fiber obtained in Example 2 for 25 minutes to obtain a mixture, then putting the mixture into a grinder and grinding it for 1.3 hours, then transferring it to a mixer and mixing it at 160° C. for 45 minutes, and drying it to obtain a nano thermal insulation material; the fumed silica (supplier: Shandong Wanhua Tianhe New Materials Co., Ltd.) and the glass fiber (supplier: Changzhou Bochao Engineering Materials Co., Ltd.);
[0054] Step S2: Stir and mix the hollow microspheres, nano thermal insulation material, perlite, coke gemstones, activated alumina powder, soft clay, high temperature cement, expansion agent and water reducer for 1.3 hours, vibrate to form, cure at room temperature for 25 hours, and then keep warm at 110°C for 25 hours to obtain an energy-saving and environmentally friendly furnace top nano thermal insulation castable; the hollow microspheres (supplier: Shijiazhuang Mayue Building Materials Co., Ltd., 30 mesh), perlite (supplier: Lingshou County Baisheng Mineral Products Co., Ltd., item number 0351), coke gemstones (supplier: Zibo Ouyihui Refractory Materials Co., Ltd.), activated alumina powder (supplier: Shanghai Yuanjiang Chemical Co., Ltd.), soft clay is soft kaolin (supplier: Shijiazhuang Huijin Mineral Products Co., Ltd.), high temperature cement (supplier: Changzhou Painuomen Thermal Conductive Materials Co., Ltd.), the expansion agent is kyanite (supplier: Henan Jingchuan Kyanite Mining Co., Ltd.), and the water reducer is sodium tripolyphosphate.
[0055] Example 6
[0056] Energy-saving and environment-friendly furnace top nano thermal insulation castable, including the following raw materials by weight: 15 parts of hollow microspheres, 4 parts of nano thermal insulation materials, 25 parts of perlite, 35 parts of coke gemstones, 7 parts of activated alumina micropowder, 7 parts of soft clay, 22 parts of high-temperature cement, 5 parts of expansion agent, and 0.4 parts of water reducing agent;
[0057] The nano thermal insulation material comprises the following raw materials in parts by weight: 80 parts of fumed silica, 30 parts of titanium dioxide, 7 parts of glass fiber, and 5 parts of modified fiber;
[0058] The energy-saving and environment-friendly furnace top nano thermal insulation castable is prepared by the following steps:
[0059] Step S1: stirring fumed silica, titanium dioxide, glass fiber and the modified fiber obtained in Example 3 for 30 minutes to obtain a mixture, then putting the mixture into a grinder and grinding it for 1.5 hours, then transferring it to a mixer and mixing it at 170° C. for 50 minutes, and drying it to obtain a nano thermal insulation material; the fumed silica (supplier: Shandong Wanhua Tianhe New Materials Co., Ltd.) and the glass fiber (supplier: Changzhou Bochao Engineering Materials Co., Ltd.);
[0060] Step S2: Stir and mix the hollow microspheres, nano thermal insulation material, perlite, coke gemstones, activated alumina powder, soft clay, high temperature cement, expansion agent and water reducer for 1.5 hours, vibrate to form, cure at room temperature for 26 hours, and then keep warm at 120°C for 26 hours to obtain energy-saving and environmentally friendly furnace top nano thermal insulation castable; the hollow microspheres (supplier: Shijiazhuang Mayue Building Materials Co., Ltd., 30 mesh), perlite (supplier: Lingshou County Baisheng Mineral Products Co., Ltd., item number 0351), coke gemstones (supplier: Zibo Ouyihui Refractory Materials Co., Ltd.), activated alumina powder (supplier: Shanghai Yuanjiang Chemical Co., Ltd.), soft clay is soft kaolin (supplier: Shijiazhuang Huijin Mineral Products Co., Ltd.), high temperature cement (supplier: Changzhou Painuomen Thermal Conductive Materials Co., Ltd.), the expansion agent is kyanite (supplier: Henan Jingchuan Kyanite Mining Co., Ltd.), and the water reducer is sodium hexametaphosphate.
[0061] Comparative Example 1
[0062] Compared with Example 6, the modified fiber is replaced with ordinary polypropylene fiber, and the rest is exactly the same as Example 6 to prepare an energy-saving and environmentally friendly furnace top nano thermal insulation castable.
[0063] Comparative Example 2
[0064] Compared with Example 6, γ-glycidyl ether silyl propyl sesquioxane was replaced with 2-toluene glycidyl ether, that is, POSS was not introduced, and the rest was exactly the same as Example 6 to prepare an energy-saving and environment-friendly furnace top nano thermal insulation castable.
[0065] Comparative Example 3
[0066] Compared with Example 6, 1,2,4-triazine-3-carboxylic acid was replaced with phenylbutyric acid, that is, triazine was not introduced, and the rest was exactly the same as Example 6 to prepare an energy-saving and environmentally friendly furnace top nano thermal insulation castable.
[0067] The energy-saving and environment-friendly furnace top nano thermal insulation castable disclosed in the present invention is further tested for its effect, and the test results are as follows.
[0068] The energy-saving and environmentally friendly furnace top nano-insulation castables obtained in Examples 4-6 and Comparative Examples 1-3 were tested for compressive strength with reference to GB / T13480-2014 "Determination of compression properties of thermal insulation products for building use"; the flame retardant properties were tested according to GB8624-2012 "Classification of combustion performance of building materials and products", and the results are recorded in Table 1; Table 1: Test results
[0069]
[0070] According to the data in Table 1, the energy-saving and environment-friendly furnace roof nano-insulation castable of the present invention has excellent compressive strength, high temperature resistance and flame retardancy. It can be seen from Example 6 and Comparative Example 1 that ordinary polypropylene fiber is used in nano-insulation materials, and the compatibility of ordinary polypropylene fiber with components such as fumed silica and titanium dioxide is poor, and POSS and triazine are not introduced, so the flame retardancy and high temperature resistance of ordinary polypropylene fiber are not improved, which is not conducive to its use in nano-insulation materials, and is not conducive to the compressive strength, flame retardancy and high temperature resistance of the castable prepared using nano-insulation materials. It can be seen from Example 6 and Comparative Example 2 that POSS is not introduced into the modified fiber, the high temperature resistance of the modified fiber decreases, and the compressive strength decreases after 1250°C high temperature treatment, and it cannot be flame-retardant with triazine, and the flame retardancy of the modified fiber decreases, thereby causing the high temperature resistance and flame retardancy of the castable to decrease. Comparison of Example 6 with Comparative Example 3 shows that without introducing triazine into the modified fiber, the triazine cannot cooperate with POSS in flame retardancy, the flame retardancy of the modified fiber decreases, and the flame retardancy of the castable decreases.
[0071] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. Energy-saving and environmentally friendly furnace top nano thermal insulation castable, characterized by: The material comprises the following raw materials in parts by weight: 13-15 parts of hollow microspheres, 2-4 parts of nano thermal insulation materials, 20-25 parts of perlite, 32-35 parts of coke gemstones, 5-7 parts of activated alumina powder, 5-7 parts of soft clay, 20-22 parts of high-temperature cement, 3-5 parts of expansion agent, and 0.3-0.4 parts of water reducing agent; the nano thermal insulation material comprises the following raw materials in parts by weight: 60-80 parts of fumed silica, 20-30 parts of titanium dioxide, 5-7 parts of glass fiber, and 3-5 parts of modified fiber; The modified fiber is prepared by the following steps: Step A1: In a protective gas atmosphere, a triazine-containing carboxylic acid, ethyl acetate, pyridine and epoxy POSS are stirred to react to obtain a hydroxyl product; Step A2: reflux and stir the carboxylic acid containing a terminal double bond, DMF and dithionyl chloride to obtain an acyl chloride product; The hydroxyl product, pyridine and triethylamine are added to dimethyl sulfoxide, and stirred to obtain a mixed solution 1; the acyl chloride product is added to dimethyl sulfoxide, and stirred to obtain a mixed solution 2; the mixed solution 2 is added dropwise to the mixed solution 1, and stirred to react to obtain a functional monomer; Step A3: In a protective gas atmosphere, functional monomers and cross-linking agents are added into toluene, and organic fibers are added for sealing and irradiated with 60Co γ rays to obtain modified fibers.
2. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: The soft clay is soft kaolin, the expansion agent is selected from one of kyanite and quartz, and the water reducing agent is selected from one of sodium tripolyphosphate and sodium hexametaphosphate.
3. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A1, the usage ratio of triazine-containing carboxylic acid, ethyl acetate, pyridine, and epoxy POSS is 0.1-0.15 mol: 130-140 mL: 2-4 g: 49-51 g.
4. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A1, the triazine-containing carboxylic acid is selected from one of 1,3,5-triazine-2-carboxylic acid, 1,2,3-triazine-5-carboxylic acid and 1,2,4-triazine-3-carboxylic acid, and the epoxy POSS is γ-glycidyl ether silyl propyl sesquioxane.
5. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A2, the usage ratio of the carboxylic acid containing a terminal double bond, DMF, and thionyl chloride is 0.1-0.12 mol: 60-70 mL: 0.13-0.15 mol.
6. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A2, the carboxylic acid containing a terminal double bond is selected from one of 7-octenic acid, 9-decenoic acid and undecenoic acid.
7. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A2, the usage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide in the mixed solution 1 is 17-20 g: 0.01-0.015 mol: 0.05-0.07 mol: 80-90 mL.
8. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A2, the usage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution 2 is 15-19 g: 30-40 mL; the usage ratio of the mixed solution 1 and the mixed solution 2 is 85-95 mL: 35-45 mL.
9. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A3, the usage ratio of toluene, functional monomer, crosslinking agent and organic fiber is 400-450 mL: 35-40 g: 10-12 g: 100-110 g.
10. The energy-saving and environment-friendly furnace top nano thermal insulation castable according to claim 1, characterized in that: In step A3, the organic fiber is selected from one of polyethylene fiber and polypropylene fiber, and the cross-linking agent is divinylbenzene.
Citation Information
Patent Citations
Preparation method of POSS-DOPO-triazine derivative flame retardant with self-assembled enhancement effect and application thereof
CN107868255A
High-strength gradient heat interception castable for heat recovery coke oven door and preparation method of high-strength gradient heat interception castable
CN114249598A
Biomass carbon preparation process
CN118851157A
Nanometer micropore heat insulation plate and preparation method thereof
CN118894677A
Fireproof high-strength coke oven slurry and preparation method thereof
CN119038953A